Effects of color on the athletic performance of short-distance runners - Fujii, T.; Nakano, H.; Wakita, M.; Maeshima, E. (Journal of Athletic Enhancement, 2017)
Colors have the effect of healing and exciting us. In recent years, the number of institutions using the color red rather than blue for tartan tracks has increased. Some research has claimed that blue tartan was put into practical use with the intention of improving performance. However, there is no agreement on the influence of color on performance among runners. Subjects were divided into two groups; group A specializing in the 100-m and 200-m races and group B specializing in the 400 m race. We measured the anaerobic power and VO2max. In group A, better recordings were obtained for anaerobic power when wearing red goggles versus blue ones, while better recordings were obtained with VO2max when wearing blue goggles. In group B, we could not determine whether or not color had a positive effect on performance. We examined the effect of color on the anaerobic power and cardiopulmonary function of sprint runners in track and field.